Role of Paricalcitol in Modulating the Immune Response in Patients with Renal Disease - Santoro, Domenico; Buemi, Michele; Cernaro, Valeria; Costantino, Giuseppe; Romeo, Adolfo; Montalto, Gaetano; Iannello, Daniela; Stassi, Giovanna; Arena, Adriana; Lucisano, Silvia; Lupica, Rosaria (International Journal of Endocrinology, 2015)
Introduction. The aim was to highlight the existence of a relationship between vitamin D deficiency, chronic inflammation, and proteinuria, by measuring neutrophil gelatinase associated lipocalin (NGAL) and common inflammatory markers after administration of paricalcitol, a vitamin D analog, in vivo and in vitro. Methods. 40 patients with end-stage chronic kidney disease (CKD) and secondary hyperparathyroidism and 40 healthy subjects were enrolled. Serum calcium, phosphorus, 25(OH)-vitamin D, parathyroid hormone (PTH), erythrocyte sedimentation rate, high-sensitivity C-reactive protein, interleukin- (IL-) 17, IL-6, IL-1β, interferon-gamma (IFN-γ), tumor necrosis factor-alpha (TNF-α), plasmatic and urinary NGAL, and 24 h albuminuria and proteinuria were measured before and 24 h after an intravenous bolus of paricalcitol (5 mcg). Human peripheral blood mononuclear cells were isolated and stimulated with phytohaemagglutinin. NGAL, IL-1β, IL-17, IL-6, TNF-α, and IFN-γ were measured in the culture medium and in the 24 h urine collection. Results. 25(OH)-vitamin D was lower in CKD than in controls ( p < 0.0001 ), while inflammatory markers were higher in CKD group ( p < 0.0001 ). In vivo and in vitro studies showed a downregulation of NGAL, IL-17, IL-6, IL-1β, TNF-α, and IFN-γ after paricalcitol administration ( p < 0.0001 ). Conclusions. 25(OH)-vitamin D regulates immune and inflammatory processes. Further studies are needed to confirm these data in order to improve the treatment of CKD patients.